Protein profile of different cellular fractions from Mycobacterium tuberculosis strains after exposure to isoniazid - Nieto Ramirez, Luisa María (Data Brief, 2019)
Different biochemical studies looking for the effect of INH on the physiology of Mycobacterium tuberculosis (Mtb) have been conducted. Here, we present a detailed analysis, looking at the protein variation in the Mtb cell due to exposure of sub-inhibitory concentrations of INH, evaluating three different variables: cellular fraction, genetic lineage, and INH phenotypic profile. Mass spectrometry analysis demonstrated that the most significantly affected cellular fraction was the membrane and the INH resistant strains showed the highest number of proteins altered when they were exposed to INH. Raw data are available via ProteomeXchange with identifier PXD007588.